KONSEP LEADERSHIP PERSPEKTIF FILSAFAT SUFISTIK AL-JILLI - Selamet Susilo (stit-islamic-village, 2022)
Sufism as the core of Islamic teachings arises by providing solutions and therapies for human problems by getting closer to Allah the Creator. The opportunity of Sufism in dealing with psychological diseases of all human problems, increasingly widespread in this modern era. However, Sufism has been perceived as an inner practice that breaks away from worldliness, as well as in terms of leadership that is currently loaded with worldliness. however, if the teachings of Sufism are interpreted into the context of the nature that must be possessed by a leader, it will be visible the urgency of leadership with the framework of Sufism, as in the sufi teachings of Al-Jilli. This study uses the method of literature study by making a number of the results of previous researchers' studies as the main data source. The results of this study show that leadership is a process by which a person can become a leader (leader) through continuous activities so that it can influence the one he leads (followers) in order to achieve common goals. Although the perception that exists so far about Sufism is not so fixated on the world, it is not so with the interpretation of Sufi values in the conceptual framework of leadership. If referring to the doctrine of Sufi al-Jilli, namely his concept of the kamil man, then a leader should have criteria: (a) have the nature of jamal, (b) be aware of his duties as a servant and caliph, (c) simple, (d) attach importance to the principle of balance, (e) trust, (f) closely related to Allah, and (g) noble character.